Arab Spring: Islam in the Political Revolution and Middle Eastern Development - Ahmad Husaini (GoAcademica Research & Publishing, 2019)
The social movements that were present during the Arab Spring have caused political upheaval in Middle Eastern countries. Starting from Tunisia, the revolution spread to neighboring countries namely Egypt, Libya, and Syria. Present in the midst of a prominent Islamic religion and culture, the aim of the revolution is to bring democracy into the government systems of countries that have long been in an autocracy system, but so far democracy with Islam has often been considered incompatible with each other, especially in countries with values deep-rooted Islamic values. This article focuses on the use of Islamic values ​​in the global civil society movement that takes place in the Arab Spring. Reviewing the revolution in a macro, the main argument of the author is that the Arab Spring became a phase which brought Islam a certain degree of flexibility towards democracy and brought democracy to the Arab world. This article generates the conclusion that the trigger for the revolution was not due to religious matters, the demonstrators who joined were not one hundred percent Muslim, and the issue demanded was not related to the religious life of the people, but that Islam, whether its values ​​or religious practices, could not be separated in organizing the masses during the revolution.